RESIDUAL OPERATIONAL RESOURCE ASSESSMENT OF HIGH TEMPERATURE ELEMENTS OF POWER ENGINEERING EQUIPMENT - S. E. Khoroshilov; A. V. Nikulin; A. V. Marukhov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a specific assessment of heat resistant steel residual resource which  is  based  on  time determination of pore output on grain boundary with due account of an operational temperature, chemical composition and structure of the investigated steel.